Isolation of a High Antioxidant Non-Toxic Polar Fraction from Garcinia mangostana Fruit Pericarp by Reverse Phase Column Chromatography - Wahyuningsih Wahyuningsih; Miranti Miranti; Hilwan Yuda Teruna; Titania Tjandrawati Nugroho (Jurnal Kimia Sains dan Aplikasi, 2021)
The crude polar extract of mangosteen fruit pericarp not only has a moderate antioxidant activity of (55±4 μg/mL) but also has high cytotoxicity (16±0.5 μg/mL). The high cytotoxicity presumably is caused by the presence of complex cytotoxic compounds from the mangosteen pericarp. To obtain a non-toxic extract preparation with high antioxidant activity, polar crude 50% ethanol extracts of mangosteen pericarp were partially purified using reverse-phase column chromatography with Silica C18 as the stationary phase and acetonitrile-water gradient elution. Six of the ten fractions collected had high antioxidant activities, with IC50 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging antioxidant levels <50 μg/mL. Three fractions (fractions 3, 5, and 7) with the highest antioxidant activities of (16.4 ± 0.6 µg/mL), (17.8 ± 2 µg/mL) and (17.4 ± 1.8 µg/mL) respectively, were chosen for further cytotoxicity, phenolic content and High-Performance Liquid Chromatography (HPLC) analysis. The cytotoxic tests were conducted with the Brine Shrimp Lethality Assay. Fraction 3 had low cytotoxicity (LC50 485 ± 96 µg/mL) and fraction 5 was non-toxic (LC50 ≥ 1000 µg/mL), while fraction 7 still had high cytotoxicity (LC50 2.8 ± 0.8 µg/mL). The chromatogram profiles of HPLC showed that fractions 3 and 5 contained more polar compounds than the compounds present in fraction 7. It can be concluded that the reverse phase method succeeded in the isolation of a non-toxic polar fraction, that is, fraction 5, with a significantly higher (p<0.05) antioxidant activity than in the original crude polar extracts. This fraction had a high total phenolic content of 43.3 ± 0.3 g GAE per 100 g extract.